KUOSIEN SEMIRING DAN SEMIRING YANG DIBENTUK DARI KELAS-KELAS KONGRUENSI SUATU SEMIRING - Atika Ayuningtyas (Jurnal Matematika, 2015)
ABSTRAK. An ideal of a semiring can be formed as set of all coset of ideal semiring. The set of all coset of ideal semiring can be formed a new semiring called quotient semiring. The congruence classes on a semiring can be formed as a new semiring called semiring congruence classes.Keywords : semiring, ideal, congruence, quotient semiring, semiring classes congruence.